1997
DOI: 10.1002/(sici)1097-4644(19970301)64:3<369::aid-jcb3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Localization of group IIc low molecular weight phospholipase A2 mRNA to meiotic cells in the mouse

Abstract: We use in situ hybridization to demonstrate that the testicular expression of a novel, mouse, low molecular weight phospholipase A2 (PLA2 Group IIc) mRNA is specific to cells undergoing meiosis. A complete cDNA (1421 bp) encoding the mouse Pla2g2c gene was generated with reverse transcription-PCR (RT-PCR) and 5' and 3' RACE (rapid amplification of cDNA ends) RT-PCR, and its nucleotide sequence was determined. Northern blots of RNA from different tissues revealed a single 1.6 kb transcript only in testis. In si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…A cell biological study using Pla2g2c knockdown has shown that sPLA 2 -IIC is upregulated in hepatitis B-infected mouse hepatocytes to produce lysophosphatidylethanolamine (LPE), which is then presented to CD1d on natural killer T cells, leading to propagation of an anti-virus immune response ( 77 ). sPLA 2 -IIC is also expressed in meiotic cells in rodent testis ( 78 ). However, as sPLA 2 -IIC is a pseudogene in humans ( 12 ), analysis of Pla2g2c Ϫ / Ϫ mice has not been performed.…”
Section: S Participate In Diverse Biologicalmentioning
confidence: 99%
“…A cell biological study using Pla2g2c knockdown has shown that sPLA 2 -IIC is upregulated in hepatitis B-infected mouse hepatocytes to produce lysophosphatidylethanolamine (LPE), which is then presented to CD1d on natural killer T cells, leading to propagation of an anti-virus immune response ( 77 ). sPLA 2 -IIC is also expressed in meiotic cells in rodent testis ( 78 ). However, as sPLA 2 -IIC is a pseudogene in humans ( 12 ), analysis of Pla2g2c Ϫ / Ϫ mice has not been performed.…”
Section: S Participate In Diverse Biologicalmentioning
confidence: 99%
“…However, in mice, this isoform is exclusively expressed in the testes and particularly in cells undergoing meiosis [39]. In humans, gene encoding for GIIC is not expressed and appears to be a non-functional pseudogene [40].…”
Section: Giicmentioning
confidence: 99%
“…Expression of sPLA 2 -IIC, a rodent-specific isozyme, in mouse spermatogenic cells was also demonstrated by in situ hybridization. 89) Thus, it is tempting to speculate that these germ cell-associated sPLA 2 s may play a role in the sperm acrosome reaction by producing LPC. The possible role of sPLA 2 s in the acrosome reaction, an exocytosis event in which the acrosomal content is released prior to fertilization, is reminiscent of the ability of sPLA 2 s to promote exocytosis in mast cells and neuroendocrine cells.…”
Section: )mentioning
confidence: 99%